Network on veterinary medicines initiated by the European Federation For Pharmaceutical Sciences. Issue 3 (20th December 2017) - Mochel, J. P.; Tyden, E.; Hellmann, K.; Vendrig, J. C.; Şenel, S.; Dencker, L.; Cristina, R. T.; Linden, H.; Schmerold, I.
Abstract : The European Federation for Pharmaceutical Sciences (EUFEPS) was founded 25 years ago by more than 20 national pharmaceutical societies and faculty members. As a pan‐European organization, it brings together pharmaceutical societies as well as academic, industrial and regulatory scientists engaged in drug research and development, drug regulation and education of professionals working in these fields. EUFEPS represents pharmaceutical sciences in Europe and is recognized as such by both the European Commission and the European Medicines Agency. EUFEPS cooperates with the European Federation of Pharmaceutical Industries and other European organizations and maintains global connections with agencies such as the US Food and Drug Administration and the American Association of Pharmaceutical Scientists. EUFEPS has established specified networks forming the basis of its activities. The creation of a Network on Veterinary Medicines is prompted by the manifold problems resulting from the use of veterinary drugs and its inherent interconnections with human medicine, environmental and public health. A long‐term goal of this initiative was to expand the spectrum of available therapeutics for use in animals, including the development of innovative delivery systems.